Graphic display on altera dsp development kit cyclone III [electronic resource] - Muhammad Akram Zulkifly, author; Shaikh Nasir Shaikh Husin (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mikroelektronik)) - Universiti Teknologi Malaysia, 2011